Agrobacterium VirB10, an ATP energy sensor required for type IV secretion - Cascales, Eric (National Academy of Sciences, 2004)
Bacteria use type IV secretion systems (T4SS) to translocate DNA and protein substrates to target cells of phylogenetically diverse taxa. Recently, by use of an assay termed transfer DNA immunoprecipitation (TrIP), we described the translocation route for a DNA substrate [T-DNA, portion of the Ti (tumor-inducing) plasmid that is transferred to plant cells] of the Agrobacterium tumefaciens VirB/D4 T4SS in terms of a series of temporally and spatially ordered substrate contacts with subunits of the secretion channel. Here, we report that the bitopic inner membrane protein VirB10 undergoes a structural transition in response to ATP utilization by the VirD4 and VirB11 ATP-binding subunits, as monitored by protease susceptibility. VirB10 interacts with inner membrane VirD4 independently of cellular energetic status, whereas the energy-induced conformational change is required for VirB10 complex formation with an outer membrane-associated heterodimer of VirB7 lipoprotein and VirB9, as shown by coimmunoprecipitation. Under these conditions, the T-DNA substrate is delivered from the inner membrane channel components VirB6 and VirB8 to periplasmic and outer membrane-associated VirB2 pilin and VirB9. We propose that VirD4 and VirB11 coordinate the ATP-dependent formation of a VirB10 “bridge” between inner and outer membrane subassemblies of the VirB/D4 T4SS, and that this morphogenetic event is required for T-DNA translocation across the A. tumefaciens cell envelope.